Evaluation of LATS1 and LATS2 Promoter Methylation with the Risk of Pterygium Formation - Maryam Najafi; Dor Mohammad Kordi-Tamandani; Mohammad Arish (Journal of Ophthalmology)
Purpose. Pterygium is a serious eye problem in countries with high exposure to UV. However, despite numerous studies, the molecular etiology of pterygium is unclear. Recent studies have indicated that LATS1 and LATS2 genes are involved in DDR signaling pathways against continuous UV exposure. Our aim was to evaluate the LATS1 and LATS2 promoter methylation with the risk of pterygium formation. Methods. We evaluated the promoter methylation status of LATS1 and LATS2 using methylation-specific PCR technique. Also, mRNA expression of LATS1 and LATS2 was assessed in 14 cases of pterygium and 14 normal specimens by real-time PCR. Results. Promoter methylation of LATS1 and LATS2 was detected significantly between pterygium tissues and normal tissues [LATS1; OR = 4.9; 95% CI: 1.54 to 15.48, P=0.003; LATS2; OR = 7.1; 95% CI: 1.53 to 33.19, P=0.004]. The gene expression analysis showed a statistically significant difference between pterygium tissues and healthy controls for both LATS1 and LATS2 (P<0.05). Conclusions. The data of this study is the first report regarding the effect of promoter methylation of the LATS1 and LATS2 in the pterygium. To confirm these data, doing further studies in various genetic populations with large sample sizes using advanced molecular techniques is proposed.